Effect of Moringa oleifera consumption on diabetic rats - Villarruel-López, A. (BMC Complement Altern Med, 2018)
BACKGROUND: Therapeutic use of leaves of M. oleifera has been evaluated in diabetes because of its possible capacity to decrease blood glucose and lipids concentration after ingestion, as result of the polyphenols content and others compounds. Nevertheless most results have been obtain from leaf extract, therefore this study would use leaf powder as the regular way of consumption of population to know effects over toxicity glucose, triglycerides, cholesterol, corporal weight, and predominant groups of microbiota. METHODS: Powdered leaf was administrated in different doses to know toxicity and genotoxicity using LD50 and micronuclei assay. Hyperglycemia was induced by alloxan on Sprague Dawley rats. Glucose and body weight were measured once a week meanwhile cholesterol and triglycerides were analyzed at the end of the study by commercial kits. Different organs were examined by hematoxylin-eosin technique. Lactic acid bacteria and Enterobacteriaceae were enumerated from stool samples. RESULTS: The tested doses revealed no lethal dose and no significant differences in genotoxicity parameter. The consumption of the leaves showed a hypoglycemic effect (< 250 mg/dL in diabetic M. oleifera treated group), however in corporal weight showed an increased (> 30 g over no M. oleifera treated groups). There was no change in enumeration of lactic acid bacteria (8.4 CFU/g) but there were differences in the predominance of type of lactobacillus and enterobacteria enumeration. CONCLUSIONS: These results help to increase information over the most popular use of M. oleifera and its safety. However there are needed more studies over the hypoglycemic mechanisms and effects over intestinal microbiota.